Design and optimization of a GFRP and steel hybrid prestressed SFRC beam based on numerical and analytical approaches - Shahrbijari, Kamyar Bagherinejad (2023)
Due to corrosion immunity, GFRP bars can be used in combination with steel bars and disposed in arrangements that take advantage of their specific properties. Since steel stirrups are the most susceptible to corrosion, significant advantages can be obtained with their replacement by fiber reinforcement, using Steel Fiber Reinforced Concrete (SFRC), which also allows to decrease the thickness of the beam’s web. In addition, prestressing the flexural reinforcement increases the service load-carrying capacity of the beams and their shear strength. This study highlights the flexural performance of hybrid prestressed GFRP-Steel SFRC beams considering the optimum design provided with the use of a genetic algorithm (GA) on simply supported I-shaped beams. The results show that the proposed GA-based optimization procedure provides an effective approach to obtain the balanced reinforcement ratio for these types of beams.